2005
DOI: 10.1021/la050569j
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution 2D 1H−15N NMR Characterization of Persistent Structural Alterations of Proteins Induced by Interactions with Silica Nanoparticles

Abstract: The binding of protein to solid surfaces often induces changes in the structure, and to investigate these matters we have selected two different protein-nanoparticle systems. The first system concerns the enzyme human carbonic anhydrase II which binds essentially irreversibly to the nanoparticles, and the second system concerns human carbonic anhydrase I which alternate between the adsorbed and free state upon interaction with nanoparticles. Application of the TROSY pulse sequence has allowed high-resolution N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 36 publications
2
40
0
Order By: Relevance
“…Unlike the “hard” (very stable) protein carbonic anhydrase II, the “soft” (less stable) protein carbonic anhydrase I undergoes a larger structural rearrangement when adsorbed onto silica nanoparticles, as shown by NMR. 171 The size of silica nanoparticles determines the surface curvature, which influences protein adsorption and the stability of the adsorbed proteins. For instance, larger nanoparticles cause a greater loss of α helicity and enzymatic activity in bound lysozyme 172 and induce a greater decrease in the thermodynamic stability of RNase A.…”
Section: Nanoparticle-biomolecule Interactionsmentioning
confidence: 99%
“…Unlike the “hard” (very stable) protein carbonic anhydrase II, the “soft” (less stable) protein carbonic anhydrase I undergoes a larger structural rearrangement when adsorbed onto silica nanoparticles, as shown by NMR. 171 The size of silica nanoparticles determines the surface curvature, which influences protein adsorption and the stability of the adsorbed proteins. For instance, larger nanoparticles cause a greater loss of α helicity and enzymatic activity in bound lysozyme 172 and induce a greater decrease in the thermodynamic stability of RNase A.…”
Section: Nanoparticle-biomolecule Interactionsmentioning
confidence: 99%
“…Besides these methods, nuclear magnetic resonance (NMR) should be able to provide data from all coupled H and N atoms in a protein 17, 59 . X-ray crystallography is also a preferred method to evaluate protein 3-D structure and protein-NP binding 58 .…”
Section: Np-single Protein Interactionsmentioning
confidence: 99%
“…The association rate constants of some complexes approach the diffusion-controlled limit, whereas conformational changes upon binding may slow down the process by orders of magnitude. Although most kinetic studies of adsorbed proteins concern extended surfaces of larger particles, reported time scales of exchange of adsorbed proteins from silica, polymer and TiO 2 nanoparticles range from 100 s to many hours (19)(20)(21)(22)(23)(24). The affinities and/or exchange rates depend on molecular details and the stability of the protein toward unfolding (19,25).…”
mentioning
confidence: 99%